A multi-agent framework for capability-based reconfiguration of industrial assembly systems. Issue 10 (19th May 2017) - Antzoulatos, Nikolas; Castro, Elkin; de Silva, Lavindra; Rocha, André Dionisio; Ratchev, Svetan; Barata, José
Abstract : Rapidly changing market requirements and shorter product lifecycles demand assembly systems that are able to cope with frequently changing resources, resource capabilities and product specifications. This paper presents a multi-agent framework that can adapt an assembly system in order to cope with such changes. The focus of this work is on the ability to plug resources (such as PLCs) into and out of the system, and dynamically aggregate resource capabilities to form more complex ones as resources are plugged in. In addition, an implementation of the framework on an industrial assembly system is discussed, and some insights are provided into some of the key features that product specification languages ought to have to be useful in real world assembly systems, and into the added value of using the proposed framework.